Pendidikan Islam Menurut Pemikiran Ahmad Tafsir dan Relevansinya dengan Pendidikan Islam Kontemporer - Violeta, Fajar Mustika; Maragustam, Maragustam; Apriari, Shinta Ath Thariq (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
Islamic education thinking provides a theoretical and practical basis for the development of an education system that is in accordance with Islamic principles, strengthens the religious identity of Muslims, and bridges the understanding of the challenges of a dynamic era. This study aims to analyze Ahmad Tafsir's thoughts on Islamic education and its relevance in the context of contemporary Islamic education. The methodology used is a literature study with a qualitative approach. Primary data comes from relevant books by Ahmad Tafsir, as well as several secondary sources such as journal articles and proceedings. Data collection techniques are done through documentation, and data analysis is done by content analysis method of Ahmad Tafsir's works. The results showed that the thought of Islamic education according to Ahmad Tafsir is based on faith as the core of the Islamic education curriculum. His thoughts are able to answer the challenges of moral degradation and are relevant to contemporary Islamic education. The implication of this research can be a foundation in evaluating modern educational practices to be in accordance with Islamic characteristics, as well as the basis for curriculum development to suit the needs of contemporary Islamic education.